Impact Assessment of Wax Gelation Fluid Pressure and Temperature: Designing Long-Term Preventive Solutions - Pamungkas, Mohd Wirawan Putra; Hasan, Meutia Fitri; Lestari, Venty; Budiman, Hendra; Setiawan, Aldo (Testing Center for Oil and Gas LEMIGAS, 2025)
Paraffinic precipitation presents a pervasive flow challenge, specifically impacting this light crude oil (API 34.85 °) system, particularly within a pipeline (length 1153 m) operating in cold environments. This study first rigorously assessed the critical impact of flow parameters, confirming the fluid’s thermal profile drops below the pour point (31.67 oC) at a crucial distance of 439.24 m from the wellhead, initiating severe wax gelation. Flow analysis further confirms a detrimental laminar flow regime (NRe = 1262), which, coupled with a significant total pressure drop of 0.155 psia/100 ft along the pipeline, exacerbates the tendency for solidified paraffins to accumulate due to insufficient shear stress. To address this, the research successfully validated a cost-effective, long-term preventative solution: a locally fabricated sand heater with an energy capacity of 175,000 kcal/h. Empirical field testing confirmed the intervention provides a substantial net thermal elevation of 8.5 oC. Subsequent thermal modeling for long-term operational reliability identified the optimal sand-heater placement distance to be within 300 m of the wellhead. This strategic placement ensures the fluid temperature consistently remains safely above the pour point, effectively mitigating the risk of premature wax gelation and guaranteeing uninterrupted system integrity and sustained hydrocarbon production.